Response of Liquid Organic Fertilizer and Type of Media on Pakcoy (Brassica Rapal.) Production by Wick Hydroponics - Yekti Puji Lestari; Helilusiatiningsih, Nunuk; Eva Pebriana (University of Jember, 2022)
A Green mustard or Pakcoy (Brassica rapa L.) is a type of vegetable that has high economic value and has the potential to contain bioactive compounds and nutrients that are useful for increasing immunity in the body. The formulation of the problem obtained is whether there is an interaction between giving POC and types of media on the development and production of pakcoy. The purpose of the experiment was to study and evaluate the response of POC and media types to pakcoy production using hydroponics. The research methodology used a completely randomized design, two factors, namely the concentration of POC (K) and the type of growing media (M). Parameters measured included plant height, leaf area, fresh weight, root length. The data were tested with ANOVA consisting of F Count and BNT Test or Duncen's test if there was a significant effect. The results of the study proved that there was no interaction between the two treatments. However, there was a single effect on media use and the best one was M2 (husk charcoal) which had the highest number of leaves, leaf area, fresh weight and root length. The addition of POC concentration of 12 ml/L had a very significant effect on the variation in leaf area observed at 30 days after planting.